(untitled) (Journal of the College of Basic Education, 2025)
The present study aimed to assess the effectiveness of a counseling program based on Meichenbaum theory in enhancing self-compassion among female dormitory students. The researchers adopted a quasi-experimental design with two groups (experimental and control) using a pre-post test. The sample consisted of 20 students, with 10 students in each group. The researchers utilized the Self-Compassion Scale developed by Al-Azzawi (2014), which includes 26 items. A counseling program consisting of 12 sessions—conducted twice a week—was developed based on the principles of Meichenbaum theory. The results revealed statistically significant differences at the 0.05 level between the experimental group’s mean scores in the pre- and post-tests, in favor of the post-test. No significant differences were found within the control group. Furthermore, statistically significant differences were found between the experimental and control groups in the post-test, favoring the experimental group. The effect size was calculated at 0.71, indicating a high level of effectiveness for the program in enhancing self-compassion. Based on the findings, the researchers concluded with a set of recommendations and suggestions.